Implementation of The Problem-Based Learning Model to Improve Students' Mathematical Problem-Solving Abilities - Alamra, Nadia Suci Wahyuni; Anggraini, Rini Dian; Solfitri, Titi (Universitas Ma'arif Lampung, 2024)
The low mathematical problem-solving abilities of Indonesian students can be seen from the PISA test results, which show that Indonesian students are ranked 72nd out of 78 countries, with an average score of 394 in 2018. Using Problem-Based Learning, this classroom action research seeks to improve the learning process and increase students' mathematical problem-solving abilities. This research was attended by 41 students with various skill levels from class VIII 3 of SMP Negeri 17 Pekanbaru. This research was divided into two cycles, each consisting of four stages: preparation, implementation, observation, and reflection. Research instruments include learning tools and instruments for collecting data. The KPMM test instruments and observation sheets are data collection instruments, while the syllabus, learning implementation plans, and student worksheets are learning tools. Data from observation sheets and mathematical problem-solving ability tests were examined using descriptive analysis techniques. From cycle I to cycle II, the learning process, according to observation data, experienced improvement. In cycle II, the average value of students' mathematical problem-solving abilities increased from 55.97 in cycle I to 81.09. By implementing Problem Based Learning in the learning process, the mathematical problem solving abilities of class VIII3 students at SMP Negeri 17 Pekanbaru have increased and improved their learning process. So researchers highly recommend this learning model in improving the learning process and increasing students' KPMM.